Moral Qualities of Contemporary Women - Baratovna, Shamaeva Muhabbat (European Journal of Life Safety and Stability (2660-9630), 2021)
Due to the socio cultural norms of the Indian society, gender mindset and discrimination internalized to an extent where our self image is partially determined by the fact that we male and female. In this tenderized Indian society women should be empowered and need to follow their role models and become worthy of emulation. With the aim of value based education, the ability to make moral judgments based on sound reasoning can deliberately be cultivated. Empowerment has to come from within and is not something which can be given. Women empowerment is a process of individual and social transformation; and begins in the mind from her own consciousness and her own rights, capabilities and potentials from herself image and awareness about development in all fields. From the social perspectives, value based education promotes effective learning and underpins the continuous improvement of personal, social, moral and economic well being. So, with the imposition of value education one can promote significant value to understanding, co – relationship and development of one’s personality with other fellow beings. All the prerequisites of women empowerment as a member of the society can be nourished with value based education. Value based education is investment in individual capability and self responsibility. Value based education refers to a wide gamut of learning and activities ranging from training in physical health, mental hygiene, etiquette and manners, appropriate social behavior, civic rights and duties to aesthetic and even religious training. This small paper is a humble attempt to study about the importance of value based education as a means for empowering women which is a great need of the hour. If women are not empowered and discriminated as before, development of the society will be very difficult. Induction method will be employed, on the bases of both primary and secondary data, for this research study.